Examination of the Role of Machiavellianism and Whistleblowing in Earnings Management (Case Study of Iran's Electric Power Distribution Companies) - Rezaei, Saeideh; Mohaghegh, Arefeh; Khosravani, Arezoo; Heydari Rostami, Karamatullah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study investigates the role of Machiavellianism and whistleblowing in earnings management within Iran's electric power distribution companies.Methodology: To achieve this objective, four main hypotheses were proposed. Data from 21 electric power distribution companies in Iran were selected to test these hypotheses. Using a cluster random sampling method, 320 questionnaires were distributed, and 297 were collected. The Delphi method was used to examine the Machiavellianism variable. Subsequently, each hypothesis involving the Machiavellianism variable was divided into four sub-hypotheses. Structural equation modeling and PLS software were utilized to examine the relationships between variables.Findings: The research results confirmed the relationship between Machiavellianism and earnings management, indicating a significant negative relationship between whistleblowing and earnings management, as well as a significant negative relationship between whistleblowing and Machiavellianism.Conclusion: Based on the research findings, it can be concluded that the presence of a whistleblowing system can partially mitigate the effects of Machiavellian individuals within an organization and prevent earnings management.